Protestants and Family Planning - Goodson, Patricia (Journal of religion and health, 1997)
There is evidence supporting the hypothesis that the historically favorable views of Protestants regarding the practice of family planning are changing among selected sub-groups. Such an attitudinal shift among Protestants has been rarely investigated by social scientists. This literature review represents an initial step in examining the phenomenon. A profile of Protestants' historical views of family planning will be presented first, followed by a discussion of the recent questioning of this group's favorable attitudes towards the practice. Additionally, research literature on contraceptive behavior and fertility patterns will provide empirical evidence supporting the hypothesis.